Lo status dello schiavo per l’islam: cenni storici, questioni terminologiche e legali (Altre Modernità, 2019)
Arabic terms and translations for “slaves” – either male or female − clearly sum up the functions assigned to them: male slaves are mostly servants, military personnel or guardians, whereas the females areusually maids or musicians-prostitutes. Historically, slavery has been allowed and practiced since the beginning of the Islamic era. In fact, the Koran regulates some aspects of it, especially related to moral issues or relationships between men and women. The Islamic Law too, and the Maliki school in particular, mentions legal cases concerning the sale of slaves (hence, it must have been aquite common business). Additionally, the events that took place in Iraq and Egypt between the 9th and 13th century prove that the power in charge made use of slaves, especially for filling specific offices in the military field. It is exactly from this sector that a new caste first emerged, and then became gradually stronger. It initially defended and later inherited the management of the Arab-Islamic empire